Perancangan Running Text Pada Toko Sarana Elektronik Dengan Kontrol Bluetooth Berbasis Android Sebagai Media - ramadhan, fajar; islamiyah, mufidatul (JURNAL SISTEM KOMPUTER ASIA, 2023)
Current technological developments are a human need, one of the technologies that is widely used to convey information is running text. Currently a lot of writing on running text still uses a USB connection, flashdisk so it requires direct contact with the running text board. This makes it difficult for users, so there are technological developments in writing running text, one of the technologies used is wireless which can communicate with Android smartphones. The tools used in inputting running text are Android, Bluetooth and a microprocessor, where the microprocessor is used as a controller and the test results show that the running text that has been designed can be an alternative solution to facilitate the delivery of information and is able to operate at a distance of 10 m without obstructions and 5 m with a barrier.